2011
DOI: 10.1098/rstb.2010.0265
|View full text |Cite
|
Sign up to set email alerts
|

Position specificity of adaptation-related face aftereffects

Abstract: It has been shown that prolonged exposure to a human face leads to shape-selective visual aftereffects. It seems that these face-specific aftereffects (FAEs) have multiple components, related to the adaptation of earlier and higher level processing of visual stimuli. The largest magnitude of FAE, using long-term adaptation periods, is usually observed at the retinotopic position of the preceding adaptor stimulus. However, FAE is also detected, to a smaller degree, at other retinal positions in a spatially inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 101 publications
1
22
0
Order By: Relevance
“…In our current experiments the MFS adaptor never overlapped spatially with the central target stimulus. Thus, to observe adaptation the position invariant neurons should be activated (for a review of position specificity of face adaptation see Zimmer and Kovács 2011). Indeed, we found that adaptation to the MFS adaptor reduced the activity in the FFA but not in the OFA.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our current experiments the MFS adaptor never overlapped spatially with the central target stimulus. Thus, to observe adaptation the position invariant neurons should be activated (for a review of position specificity of face adaptation see Zimmer and Kovács 2011). Indeed, we found that adaptation to the MFS adaptor reduced the activity in the FFA but not in the OFA.…”
Section: Discussionmentioning
confidence: 92%
“…Each trial was followed by a variable jitter ranging from 1,400 to 3,100 ms. Adaptation time was shortened compared to the psychophysical experiments (Experiment 3 and 4) in order to reduce the scanning time (Zimmer and Kovács 2011).…”
Section: Experiments 3: Adaptation To Female and Male Mfsmentioning
confidence: 99%
“…We (and many others) suggest that the reason for this is that the information integrated from one fixation to the next is information about features-such as motion and form-not light elements or pixels. As other reviews in this issue point out [16][17][18][19][20][21], the process is not like 'sticking postage stamps on a tailor's dummy', integrating detailed 'snapshots' within a trans-saccadic buffer with an external metric. This would suggest that very early stages of analysis, such as V1, should not be spatiotopic, while higher centres responsible for motion and form (including middle temporal (MT) and medial superior temporal (MST) areas) might be spatiotopic.…”
Section: Spatiotopicitymentioning
confidence: 99%
“…First, these representations could help to integrate information across separate fixations. Several of the articles in this theme issue explore the potential role of allocentric and spatiotopic reference frames in supporting visual integration and visual memory updating [8,35,36]. Second, non-oculocentric representations might be important for sensorimotor and multisensory interactions that underlie multimodal properties such as visuo-haptic shape [37,38] and audio-visual movement [39,40].…”
Section: Neural Mechanisms Of Visual Stability: Remapping and Spatiotopymentioning
confidence: 99%